Indigenous technical knowledge (ITKs) for successful animal husbandry in cold deserts of Ladakh valley in Indian Himalalyas - KUMAR, KRISHAN; KHOSLA, P K; DUTT, N; FARHANA, M (The Indian Journal of Animal Sciences, 2019)
The sustained livelihood of the inhabitants of cold deserts area have heavy dependence on animal husbandry which is traditionally practiced through the adoption of rich traditional knowledge concerning animal husbandry. This Indigenous Technical Knowledge (ITK) is widely used since generations and has shown its usefulness through successful animal husbandry in these harsh region of the country. There is need for proper documentation of ITKs for proper understanding, assessing and refining on scientific principles. It will also help in conservation of rich traditional knowledge hitherto practiced but now the most threatened resource of dry temperate region. The present study therefore aimed at the documentation and possible scientific explanation for the most practiced ITKs in cold deserts of Ladakh region. Participatory Rural Appraisal tools were used for the present study.